Kenya : Accounting and Auditing - World Bank (Washington, DC, 2013)
This report assesses accounting and auditing practices in Kenya in relation to the requirements of the International Accounting Standards (IASs) issued by the International Accounting Standards Board (IASB), and the International Standards on Auditing (ISAs) issued by the International Federation of Accountants (IFAC). The report addresses the institutional capacity needed to ensure compliance with the international standards and to improve the quality of financial reporting in the country. It highlights strengths and weaknesses of the institutional framework and presents an action plan for institutional capacity building. Kenya has recently made progress in closing the gap between national accounting and auditing practices and international standards, notably by adopting the IASs and ISAs as national requirements. However, its compliance with these requirements is partial, due to enforcement mechanisms that continue to evolve and inadequate resources. In spite of these difficulties, institutional investors in Kenya perceive that the quality of financial reporting has significantly improved over the past 12 months. However, the legal framework governing accounting and financial reporting, the professional education and training arrangements, the professional body, and the enforcement mechanism need improving. Stakeholders in the country believe that successful completion of appropriate capacity-building initiatives, through implementation of an action plan, would help develop accounting and auditing practices and improve compliance with international standards within a period of three to five years.